Effect of Exposure Time of Triiodothyronine (T3) Hormone Solution on Development, Growth and Survival Rate of Giant Gouramy (Osphronemus gouramy Lac.) - Sakdiah, M.; Junior, M. Zairin; Carman, O. (Indonesian Society of Scientific Aquaculture (ISSA), 2003)
ABSTRACTThe objectives of this research were carried out to determine exposure time of giant gouramy larvae in triiodothyronine (T3) hormone solution on development, growth and survival rate. One-day old larvae were immersed in 0,1 ppm T3 hormone solution for 0, 2, 4, 6, 8, 16, and 24 hours. Results showed that treated larvae developed faster than control larvae. At first, second, fifth, sixth and seventh week, larvae that immersed in T3 hormon solution had total length longer than that of control. Treated larvae had average body weight heavier than that of control until seven weeks of experiment. Immersion of larvae for 16 hours gave the best result in term of length and average body weight. The best survival rate of larvae were obtained from 8 hours treatment.Key words : Giant gouramy larvae, triiodothyronine, exposure time, growth and survival rate. ABSTRAKPenelitian ini dilakukan untuk menentukan lama perendaman di dalam larutan hormon triiodotironin (T3) terhadap perkembangan, pertumbuhan dan kelangsungan hidup larva ikan gurame. Larva ikan yang berumur satu hari direndam dalam larutan hormon triiodotironin 0,1 ppm dengan lama perendaman 0, 2, 4, 6, 8, 16, dan 24 jam. Perkembangan larva yang diberi perlakuan T3 lebih cepat daripada perkembangan larva kontrol. Larva yang direndam dalam larutan hormon T3 lebih panjang daripada kontrol pada minggu ke-5, 6 dan 7. Bobot rata-rata larva perlakuan lebih besar daripada bobot rata-rata kontrol dari minggu awal sampai minggu ke-7. Perendaman larva selama 16 jam memberikan hasil terbaik dari segi panjang total dan bobot rata-rata. Nilai kelangsungan hidup terbaik di akhir penelitian diperoleh pada perendaman selama 8 jam. Kata kunci: Larva gurame, triiodotironin, lama perendaman, pertumbuhan dan kelangsungan hidup.